Mesentrial Cyst Lymphangioma in 3-Year-Old Girls: A Case Report - Hafni Zuchra Noor; Nunik Agustriani (Berkala Kedokteran, 2020)
Abstract: Mesenterial cysts are rare tumors, incidence 1: 100,000-200,000. We report the case and the treatment. Case report, 3-year-old woman with complaints of a lump in the abdomen. Complaints in the last 1 year ago, sometimes she felt pain, physical examination showed a lump of cystic impression with a size of ± 5x10 cm in the epigastric region, mobile, firm boundary. It can be diagnosed with a suspected intra-abdominal tumor with a mesenterial cyst, differential diagnosis of teratoma. Surgery was performed and a mass was found in retroperitoneal with a size of ± 20x5 cm up to the pelvic cavity, cystic and mobile, the mass could not be taken at all, we decided to do marsupialization, and left kidney is not visible. Postoperative diagnosis is retroperitoneal (type IV) mesenterial cyst lymphangioma with agenesis ren sinistra. Mesenterial cyst Lymphangioma is a tumor that is very rarely found and is benign. For a good prognosis, it depends on the type and therapy that is performed. Keywords: Mesenterial cyst lymphangioma, a tumor in children, mesenterial tumor